Safety of Cohesive Polydensified Matrix Cross-Linked Hyaluronic Acid Volumizing Gel in Temporal Hollows and Cheeks: A Prospective, Open-Label, Postmarket Study. Issue 10 (October 2021) - Pavicic, Tatjana; Sattler, Gerhard; Prager, Welf; Fischer, Tanja; Gauglitz, Gerd; Hofmann, Matthias; Dersch, Hanna; Riaz, Shahbaz; Kerscher, Martina
Abstract : BACKGROUND: Facial aging is characterized by volume loss and progressive hollowing of temples and cheeks. Biodegradable filler materials are preferred over nonabsorbable materials; of these, hyaluronic acid (HA) fillers are the most often used because of their favorable effectiveness and safety profile. OBJECTIVE: To confirm the safety and effectiveness of Cohesive Polydensified Matrix (CPM)-HA26 gel in the treatment of volume deficiency. METHODS: Subjects received up to 2 treatments in the temples and/or cheeks. A blinded investigator assessed improvement according to the Merz Temple Volume Scale (MTVS) and Merz Cheek Fullness Assessment Scale (MCFAS). Subjects were followed for 48 weeks after the last treatment. RESULTS: In total, 87 healthy subjects were enrolled. The proportion of subjects achieving at least a 1-grade improvement on MTVS and/or MCFAS was above 70% for each (MTVS: Weeks 4, 24, and 48 = 95.4%, 94.2%, and 77.0%; MCFAS: Weeks 4, 24, and 48 = 92.3%, 83.1%, and 71.8%). Based on MTVS and MCFAS scores at Visit 5, improvement remained visible at up to 48 weeks. No treatment-related serious AEs occurred. CONCLUSION: CPM-HA26 demonstrated both a favorable safety and effectiveness profile, with improvement in facial volume evident for up to 48 weeks. It was well tolerated and had a positive, long-lasting effect.